The Unseen Engine of Trust A Deep Dive into the RSA Algorithm (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This analysis offers a thorough overview of the RSA algorithm, a key element of modern digital security that addresses the historic challenge of secure communication over insecure public channels. Its innovation is based on number theory, using a "trapdoor" one-way function reliant on the significant computational difference between multiplying large prime numbers and factoring their product. Paired with modular arithmetic and Euler's Totient Theorem, this enables the practical use of public-key cryptography, where a public key encrypts data that only the matching private key can decrypt. The text highlights RSA's vital role in internet security, especially in securing web connections via SSL/TLS and ensuring authenticity and integrity with digital signatures. It discusses the cybersecurity arms race, stressing the importance of sufficient key lengths and secure practices to fend off classical attacks. The analysis also examines RSA's main vulnerability: the threat from quantum computing. Shor's algorithm can efficiently solve the integer factorisation problem, making RSA obsolete and prompting a global shift to Post-Quantum Cryptography (PQC). Despite its eventual replacement, RSA's legacy as the first framework that enabled trust in the digital world remains a monumental achievement in computer science.